A policy landscape analysis of the school-based vaccination program in the Philippines a case study in Region IV-A - Palola, Tricia Kaye F. (Manila College of Public Health, University of the Philippines Manila, 2025)
School-based immunization (SBI) has emerged as a strategic approach to increase vaccine coverage among school-aged children. SBI was introduced in the Philippines in 2013 to complement routine immunization and capture missed childhood vaccinations. However, coverage has continued to decline since 2015, further compounded by the 2019 polio outbreak, the Dengvaxia controversy, and prolonged COVID-19 school closures. Implementing SBI is inherently complex. Although national guidelines from the Department of Education (DepEd) and the Department of Health (DOH) aim to streamline processes, actual implementation unfolds across multiple levels - from national policy formulation to district and school-level execution.

This study employed an analytical research design utilizing policy document reviews, records analysis, and key informant interviews to examine the current level of implementation and integration of SBI across local government units (LGUs) in the First District of Rizal, Region IV-A. It also explored the facilitating and constraining factors influencing SBI implementation. Finally, the study identified critical policy gaps that undermine the program's overall effectiveness. Data were analyzed thematically to generate key themes.

The study identified critical gaps in the implementation of SBI, particularly in vaccine coverage, uptake, and data integration. Despite SBI's intended role as a catch-up mechanism, its effectiveness is limited by fragmented governance, inconsistent intersectoral coordination, and weak health information systems. While national policies provide a guiding framework, local implementation varies widely across LGUs.

Challenges include unclear stakeholder roles, logistical constraints, limited parental involvement, and minimal engagement from the private sector and local school boards. The absence of formal integration with community-based immunization programs and rising vaccine hesitancy further weaken the program's reach and sustainability.

To strengthen SBI, the study recommends structural reforms focused on improving system integration, strengthening local capacity, and revising policies to ensure more coherent, coordinated, and effective vaccine delivery across all levels of governance.
Includes references and annexes.
Thesis
Keywords: School health -- Government policy -- Case studies. -- Philippines .; Immunization programs -- Government policy -- Case studies. -- Philippines; Public health -- Government policy -- Case studies. -- Philippines .; $a Philippines -- $x Health policy -- $v Case studies